Effect of Workload and Competence on Nurses’ Performance with Supervision Moderation in Cengkareng - Sugino Kesuma Karo Karo Samura; Dewi Sandra; Nofierni Nofierni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Introducion The performance of nurses is a critical determinant of hospital service quality, influenced by multiple factors such as workload, competence, and supervision. This study aimed to analyze the effect of workload and nurse competence on nurse performance with supervision as a moderating variable at X Hospital. Methods The research employed a quantitative approach with a causal survey design. Data were collected using structured questionnaires distributed to 176 nurses and analyzed through Structural Equation Modeling (SEM) with SmartPLS 4.0. Result The findings revealed that both workload and competence significantly influenced nurse performance, with competence showing a strong positive effect. Workload was also found to have a significant effect on supervision, and nurse competence significantly enhanced supervision quality. However, supervision did not function as a moderating factor in the relationship between workload and nurse performance, nor between competence and nurse performance. Similarly, supervision itself was not significantly associated with nurse performance. The coefficient of determination showed that workload, competence, and supervision jointly explained 60% of nurse performance, while the remaining 40% was influenced by other unmeasured factors. Conclusion, workload and competence are proven to be direct determinants of nurse performance, whereas supervision in its current form does not enhance these effects. Hospital management should therefore focus on optimizing workload distribution, strengthening nurse competencies through continuous training, and reformulating supervision methods to be more participatory and supportive. These strategies are expected to improve the quality and effectiveness of nursing services and ensure sustainable improvements in hospital performance outcomes.